Octavio Paz, Memorias y palabras: cartas a Pere Gimferrer 1966-1997. Seix Barral, Barcelona, 1999; 425 pp. - Stanton, Anthony (El Colegio de México, 2001)
Se reseñó el libro: Memorias y palabras: cartas a Pere Gimferrer 1966-1997.